Percepción del maltrato y niveles de estrés en estudiantes de medicina en Cajamarca. - Rabanal-Vásquez, P.G. (2023)
Objective: To establish whether the perception of abuse was related to the prevalence of stress in the year 2024. Material and Methods: The type of study was quantitative, cross-sectional and correlational in design. 85 students were evaluated, they were selected by non-probabilistic sampling for convenience, a significant p < 0.05 was used as a parameter to determine the relationship between variables. Results: a prevalence of high levels of stress of 82.3% was found in the students, which is related to different types of abuse, academic abuse with a significant correlation with a (p = 0.020); psychological abuse with a (p = 0.0282); On the contrary, physical abuse with a (p = 0.52) and sexual abuse with a (p = 0.2308) showed no significant correlation. Sex and year of study demonstrated a significant relationship with stress levels, with values of p = 0.0274 and p = 0.0492, respectively. Regarding stress levels, a deep stress rate of 65.88% was obtained, being the most frequent to occur, followed by zero stress with 17.65% and moderate stress with 16.47%. of the 70 cases that did present stress. Conclusion: There were two types of abuse, in addition to the variables sex and year of study, significantly associated with the presence of stress levels.